Variation Characteristics of the Main Hydrochemical Indexes in Typical Subterranean Rivers in the South China Karst Region Based on Curve Fitting - Shuyi Liu; Chuan Liang; Lina Wang; Lingwei Zeng; Chunyi Wang (The Scientific World Journal)
The water quality of subterranean rivers in the South China Karst region has undergone dramatic changes resulting from industrial and social development over the past 60 years. The combination of sampling results from subterranean rivers in four typical study areas in the South China Karst region from October to December 2015 (dry season) and correlation analysis using SPSS revealed that the main ions K+, Na+, and SO42- exhibited a significant correlation (p<0.01) and that Ca2+, HCO3-, and Mg2+ exhibited a good correlation (p<0.01). Additionally, we consolidated the data collected since 1960 and, by applying MATLAB, a variety of fitting curve methods were used to fit all the data, and the results showed that cubic spline interpolation fitting performed the best. The squared correlation coefficients (R2) of the obtained fitting curves for Ca2+, HCO3-, and Mg2+ are 0.8545, 0.8689, and 0.7632, respectively, and the corrected R2 values are 0.6739, 0.7088, and 0.4853, respectively. The R2 values of the obtained fitting curves for K+, Na+, Cl-, SO42-, and NO3- are 0.9085, 0.8964, 0.7531, 0.6222, and 0.7997, respectively, and the corrected R2 values are 0.7904, 0.7669, 0.5272, 0.2815, and 0.6127, respectively, indicating excellent fits. Based on the fitting curves, the overall water quality conditions in the karst region were analyzed and compared. Finally, the development of subterranean rivers in the South China Karst region was determined. Based on the results, the following conclusions can be drawn: the development of the subterranean rivers is indeed a slow process, but water quality can change rapidly in response to the transformation of industrial society. Additionally, the results indicate the crucial importance of urban planning that takes into account environmental protection during development in karst regions. This study aims to provide a basis for the management of karst areas and the improvement of groundwater quality by evaluating geochemical processes.